The Educational Crisis as A Result of COVID-19 And the Reaction of Students Taking Their A Levels - Ewa SKRZETUSKA; Urszula DUBEJKO (Communications of International Proceedings, 2021)
The article is based on the research carried out among first-year students of pedagogy who participated in distance education in the last year of secondary school, before their final exams. The respondents' reactions to the unexpected change in the way of learning were described below. The leaving exam was supposed to take place in the first days of May, and in fact, it took place at the beginning of June 2020, due to the COVID-19 pandemic. The respondents learned about the need for distance learning in mid-March, 2 months before the end of school education. Everyone passed the matriculation examination, but not all were satisfied with the results. The reactions were varied, the analysis of the statements made it possible to observe a gradual change of opinion during the preparation for the exam and reflection on the effectiveness of remote education in preparation for the exam. On the basis of the obtained data, a model of adaptation to sudden change in the way of preparation for an important for life choices exam was formed and the factors contemporaneous with the subjective assessment of the consequences of this situation were described.
Keywords: Distance education; remote learning; COVID-19 pandemic; final exam; A-level; emotional reactions